2022
DOI: 10.3390/jcm11092355
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Primary Melanomas: Retrospective Review in a Tertiary Care Hospital

Abstract: Multiple primary melanomas (MPM) refer to the occurrence of more than one synchronous or metachronous melanoma in the same individual. The aim of this study was to identify the frequency of MPM and describe the clinical and histopathologic characteristics of patients with MPM. An observational single-center retrospective study was designed based on a cohort of melanoma patients followed in a tertiary care hospital. Fifty-eight (8.9%) patients developed MPM. Most patients were men (65.5%) and the median age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 39 publications
1
10
1
Order By: Relevance
“…High-risk CDKN2A germline mutations have been associated with an increase in subsequent melanoma risk [5]. MPM's incidence is reported between 1.2 and 13%, while SM's is estimated at 13-30% of MPM [1,7,8,11]. Although in our series patients with MPM represented 3.4%, the percentage of patients with SM was higher than usually reported (40.2%).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…High-risk CDKN2A germline mutations have been associated with an increase in subsequent melanoma risk [5]. MPM's incidence is reported between 1.2 and 13%, while SM's is estimated at 13-30% of MPM [1,7,8,11]. Although in our series patients with MPM represented 3.4%, the percentage of patients with SM was higher than usually reported (40.2%).…”
Section: Discussioncontrasting
confidence: 59%
“…Most studies report head and trunk as the most common anatomic site of first melanoma in patients with MPM [9,11]. In our series, trunk was the most common site in both groups.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…[32,51] Moreover, several studies suggested that there could be a genetic predisposition for MPM and that gene CDKN2A and CDK4 could be involved. [52][53][54] CDKN2A gene mutations are Ariyan et al [26] Trunk Trunk NR NR NR NR Beardmore et al [27] Trunk Trunk NR NR NR NR Brobeil et al [18] NR NR 2.27 0.90 NR NR Burden et al [28] NR NR 2.1 1.2 NR NR Burljan et al [29] Trunk Trunk 3.1 1.3 SSM SSM Cascinelli et al [30] NR NR NR NR NR NR Chen et al [17] Limbs NR NR NR SSM NR De Giorigi et al [20] NR NR 0.51 0.64 NR NR Ferrerres et al [31] Trunk NR 1.41 0.34 SSM SSM Ferrone et al [32] Trunk Extremities 1.2 0.4 NR NR Goggins et al [33] NR NR NR NR NR NR Helgadottir et al [34] Trunk NR NR NR NR NR Hwa et al [35] Trunk Trunk NR NR SSM SSM Johnson et al [36] Trunk NR 0.98 0.90 NR NR Kang et al [37] Trunk Trunk 1.21 0.51 SSM SSM Lallas et al [38] NR NR 1.92 0.49 NR NR Manganoni et al [21] Trunk Trunk 1.31 0.66 NR NR Menzies et al [22] Lower limbs Lower limbs 1.21 0.36 SSM SSM Moore et al [39] Head and neck Head and neck 1.05 0.83 SSM SSM Moseley et al [40] Trunk Extremities NR NR NR NR Muller et al [41] NR NR NR NR NR NR Nashan et al [23] NR Lower limbs NR 0.59 NR NR Nosrati et al [42] NR NR 2.2 1.1 NR NR Palacios Diaz et al [43] Trunk Trunk 1.54 0.65 SSM SSM Pastor-Tomas et al [14] Trunk Trunk NR NR SSM SSM Savoia et al [19] Trunk Trunk 2.2 0.64 SSM SSM Scheibner et al [44] Trunk Trunk NR NR SSM SSM Schmid et al [45] Trunk Trunk 1.6 0.7 SSM NR Siskind et al [46] Trunk Trunk 0.82 0.85 SSM SSM Stam-Posthuma et al [13] Trunk Trunk 1.11 0.9 SSM SSM Titus-Ernstoff et al…”
Section: Discussionmentioning
confidence: 99%
“…Ferrone et al [32] USA 1996-2002 385/4484 (8.6%) 139 (36%) NR 2.3 Goggins et al [33] USA 1973-1997 1421/61 245 (2.3%) 313 (22%) NR NR Helgadottir et al [34] Sweden 1960-2004 44 2469/54 884 (4.5%) NR NR NR Hwa et al [35] USA 2002-2008 61/788 (7.7%) NR 7 NR Johnson et al [36] USA 1990-1995 60/1482 (4%) 18 (30%) 7 2.4 Kang et al [37] USA 1965-1989 41/2032 (2%) 16 (39%) 5 NR Lallas et al [38] Greece 2013-2018 46/977 (4.7%) NR 6 NR Manganoni et al [21] Italy 1996-2006 47/1240 (3.7%) 10 (21%) 10 2.4 Menzies et al [22] Ireland 1994-2016 99/2057 (4.8%) 6 (13%) 10 2.5 Moore et al [39] USA 1996-2011 1122/16 570 (6.7%) NR >4 NR Moseley et al [40] USA 1971-1979 38/712 (5.3%) 12 (31%) 8 NR Muller et al [41] Austria 1968-2015 48 299/1648 (18.1%) NR >4 NR Nashan et al [23] Germany NR 30/535 (5.6%) NR NR NR Nosrati et al [42] USA 1985-2013 305/7268 (4.2%) 68 (22%) 13 2.3 Palacios Diaz et al [43] Spain 2014-2022 58/646 (8.9%) 20 (34%) 5 2.2 Pastor-Tomas et al [14] Spain 2000-2015 55/1447 (3.8%) NR NR NR Savoia et al [19] Italy 1974-1997 49/2470 (2%) 21 (43%) 6 NR Scheibner et al [44] Australia 1951-1980 90/3128 (2.9%) Aprox. 33% 5 NR Schmid et al [45] Germany 1977-1992 152/4597 (3.3%) 58 (37%) NR NR Siskind et al [46] Australia 1982-1990 221/1083 (20.4%) 13 (5%) 9 NR Stam-Posthuma et al [13] Netherlands 1983-1995 56/820 (6.8%) 13 (23%) 9 2.8 Titus-Ernstoff et al [47] USA NR 27/354 (8.0%) 8 (29%) 3 2.1 Ungureanu et al [24] Romania 2004-2020 26/699 (3.7%) 13 (50%) 4 2.3 van der Leest et al [48] Netherlands 1989-2008 1840/57 465 (3.2%) NR NR NR Villani et al [49] Italy 2014-2018 64/773 (8.2%) NR 6 NR Wassberg et al [25] Sweden 1958-1988 243/20,354 (1.1%) NR NR NR Wiener et al [50] USA 1998-2012 5960/152,811 (3.9%) 1743 (29%) NR NR MPM = multiple primary melanomas, NR = not reported.…”
Section: Authormentioning
confidence: 99%